TERORISME DITINJAU DARI PERSPEKTIF HUKUM PIDANA ISLAM (FIQIH JINAYAH) - Zulkifli Zulkifli; Muh. Syarif Hasyim; Hamiyuddin Hamiyuddin (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2020)
The discussion in this research is terrorism from the perspective of Islamic criminal law (fiqih jinayah). The problem that becomes the focus of research is how terrorism is in the review of Islamic criminal law or jinnayah fiqh. Qualitative research, the source of which is library research, is the method used in research. There are two kinds of data sources in this research, namely primary and secondary data sources, while the data collection and analysis uses literature review research. The data were analyzed using the Islamic criminal law theory approach. So as a result of this research that acts of terrorism are not justified in Islamic teachings. The birth of this action is because the perpetrators have shallow thoughts or have very minimal thoughts and have political goals to harm themselves and others. They even consider this act as Jihad, even though in fact it is not a jihad but an act that brings fear to potential victims.